Compact, Broadband and Low-Loss Polarization Beam Splitter on Lithium-Niobate-On-Insulator Using a Silicon Nanowire Assisted Waveguide - L. Zhang; L. Zhang; X. Fu; L. Yang (IEEE Photonics Journal, 2020)
We propose a compact, broadband, and low-loss polarization beam splitter (PBS) based on an asymmetrical directional coupler on the lithium-niobate-on-insulator platform, consisting of an amorphous silicon (a-Si) assisted waveguide, and a normal waveguide. With proper design of the a-Si nanowire, and lithium niobate waveguides, the phase-matching condition is satisfied for TE polarization, while significant mismatching exists for TM polarization. A 16-μm-long PBS (including the s-bend region) with a 200 nm gap is achieved. Numerical simulations show that the PBS exhibits a 140-nm bandwidth for extinction ratios larger than 10 dB. Moreover, the device has an ultra-low insertion loss (IL ~ 0.05 dB), and maintaining ILs <; 0.5 dB over a 170 nm wavelength range.